1999
DOI: 10.1046/j.1432-1327.1999.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Type‐II 3‐oxoacyl‐CoA thiolase of the nematode Caenorhabditis elegans is located in peroxisomes, highly expressed during larval stages and induced by clofibrate

Abstract: We examined the expression and localization of type-II 3-oxoacyl-CoA thiolase in the nematode Caenorhabditis elegans. Type-II thiolase acts on 3-oxoacyl-CoA esters with a methyl group at the a carbon, whereas conventional thiolases do not. Mammalian type-II thiolase, which is also termed sterol carrier protein x (SCPx) or SCP2/3-oxoacyl-CoA thiolase, is located in the peroxisomes and involved in phytanic acid degradation and most probably in bile acid synthesis. The nematode enzyme lacks the SCP2 domain, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Afterwards, little attention was paid to nematode peroxisomes. In previous studies, we have shown that type II 3-oxoacyl-CoA thiolase and catalase-2 are immunocytochemically localized to peroxisomes of Caenorhabditis elegans (Maebuchi et al 1999;Togo et al 2000), confirming that peroxisomes exist in the nematode. Caenorhabditis elegans is one of the most important experimental animals in genetic and molecular biology and a study on targeting signals of enzymes in nematode peroxisomes has been started (de Vet and van den Bosch 2000;Gurvitz et al 2001;Motley et al 2002).…”
Section: Introductionsupporting
confidence: 57%
“…Afterwards, little attention was paid to nematode peroxisomes. In previous studies, we have shown that type II 3-oxoacyl-CoA thiolase and catalase-2 are immunocytochemically localized to peroxisomes of Caenorhabditis elegans (Maebuchi et al 1999;Togo et al 2000), confirming that peroxisomes exist in the nematode. Caenorhabditis elegans is one of the most important experimental animals in genetic and molecular biology and a study on targeting signals of enzymes in nematode peroxisomes has been started (de Vet and van den Bosch 2000;Gurvitz et al 2001;Motley et al 2002).…”
Section: Introductionsupporting
confidence: 57%
“…Although conditions for DAB staining of C. elegans peroxisomes at a lower pH have not yet been established, they were detectable with anti‐(catalase‐2) serum. Using this method, type‐II thiolase of this organism was demonstrated to be a peroxisomal enzyme [22] similar to its mammalian counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…[22]. Procedures for electron microscopy, immunostaining with primary antibodies and secondary gold probes, and determination of the labeling density (gold particles per µm 2 ) were as described previously [22]. Sequences similar to catalase‐2 were searched and analyzed using the ssearch program of DDBJ.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the results using the nematode PEX-TPR domain revealed that SKI did not behave as a negative interacting partner compared with SKL (bottom cluster; Table 4). This was not very surprising because C. elegans contains at least one SKI-terminated peroxisomal protein, P-44, that is thought to be involved in phytanic acid degradation and bile acid synthesis (Bun-Ya et al 1997;Maebuchi et al 1999). Both HKL and HRL were at least as ecient as SKL in interacting with the nematode PEX-5 TPR domain (3.0-and 1.8-fold more ecient than SKI).…”
Section: Resultsmentioning
confidence: 99%